Injection rates and cost estimates for CO2 storage in the west Mediterranean region - Carneiro, Júlio (2016)
The COMET project aimed at studying the development of an integrated CO2 transport and storage infrastructure for Morocco, Portugal and Spain, and included the assessment of existing storage opportunities and capacities. Those countries have, jointly, enough capacity to store almost 200 years of their current CO2 emissions, but defining a cost-effective infrastructure implies establishing the storage costs at each potential site. This article describes the methodology pursued and the results of that cost assessment, including the estimates made for the annual injection rate and number of admissible wells at each site. Several analytical solutions describing the pressure build-up with CO2 injection were applied and a total injection rate of 558 MtCO2/a was found for the study area, although many potential sites are uneconomical due to presenting a very low injection rate. The storage costs spread over a very broad spectrum of values, but around 50 % of the injection sites show storage costs below 10 €/tCO2. Of the 43 storage clusters defined in the study area, about 11–15 are cost-effective, depending on the emission mitigation scenario, and should be the focus of future research.